A nomenclatural and taxonomic review of the names and new combinations published between 1881 and 1930 in the genus Kitchingia, basionym of Kalanchoe subg. Kitchingia (Crassulaceae subfam. Kalanchooideae), by John Gilbert Baker (1834–1920), Otto Stapf (1857–1933), and Alwin Berger (1871–1931) - Smith, Gideon F. (Phytotaxa, 2024)
During a long career as a botanist in the Herbarium of the Royal Botanic Gardens, Kew, United Kingdom, John Gilbert Baker (1834–1920) described one new genus, Kitchingia, in Crassulaceae subfam. Kalanchooideae, and eight species in this genus. He in addition published a new combination in Kitchingia for a species originally published in Kalanchoe. Otto Stapf (1857–1933), Austrian-born Kew botanist, described one new species of Kitchingia, and Alwin Berger (1871–1931), the German-born succulent plant expert, published two new combinations in Kitchingia. The genus Kitchingia was in the past variously upheld in Crassulaceae subfam. Kalanchooideae, but is today recognised in Kalanchoe at the rank of subgenus, as Kalanchoe subg. Kitchingia. The nomenclature and taxonomy of the names published in or transferred to Kitchingia by Baker, Stapf, and Berger are reviewed and discussed in a historical context. Where necessary, the names are typified.